The Arabidopsis RLCK VI_A2 Kinase Controls Seedling and Plant Growth in Parallel with Gibberellin - Valkai, Ildikó; Kénesi, Erzsébet; Domonkos, Ildikó; Ayaydin, Ferhan; Tarkowská, Danuše; Strnad, Miroslav; Faragó, Anikó; Bodai, László; Fehér, Attila (International journal of molecular sciences, 2020)
The plant-specific receptor-like cytoplasmic kinases (RLCKs) form a large, poorly characterized family. Members of the RLCK VI_A class of dicots have a unique characteristic: their activity is regulated by Rho-of-plants (ROP) GTPases. The biological function of one of these kinases was investigated using a T-DNA insertion mutant and RNA interference. Loss of RLCK VI_A2 function resulted in restricted cell expansion and seedling growth. Although these phenotypes could be rescued by exogenous gibberellin, the mutant did not exhibit lower levels of active gibberellins nor decreased gibberellin sensitivity. Transcriptome analysis confirmed that gibberellin is not the direct target of the kinase; its absence rather affected the metabolism and signalling of other hormones such as auxin. It is hypothesized that gibberellins and the RLCK VI_A2 kinase act in parallel to regulate cell expansion and plant growth. Gene expression studies also indicated that the kinase might have an overlapping role with the transcription factor circuit (PIF4-BZR1-ARF6) controlling skotomorphogenesis-related hypocotyl/cotyledon elongation. Furthermore, the transcriptomic changes revealed that the loss of RLCK VI_A2 function alters cellular processes that are associated with cell membranes, take place at the cell periphery or in the apoplast, and are related to cellular transport and/or cell wall reorganisation.
Keywords: proteiny huseníčku; transkripční faktory bHLH; transkriptom; semenáček; protein-serin-threoninkinasy; vývojová regulace genové exprese; Arabidopsis; Gibberellins; Protein Serine-Threonine Kinases; Basic Helix-Loop-Helix Transcription Factors; Gene Expression Regulation, Developmental; regulátory růstu rostlin; Transcriptome; Arabidopsis Proteins; kyseliny indoloctové; kotyledon; DNA vazebné proteiny; stanovení celkové genové exprese; regulace genové exprese u rostlin; Gene Expression Profiling; hypokotyl; DNA, Bacterial; Plants, Genetically Modified; DNA bakterií; Transcription Factors; Plant Growth Regulators; Indoleacetic Acids; transkripční faktory; Gene Expression Regulation, Plant; inzerční mutageneze; Seedlings; Hypocotyl; geneticky modifikované rostliny; gibereliny; Cotyledon; DNA-Binding Proteins; Mutagenesis, Insertional